Budidaya Ulat Sutera Daun Singkong Hasil Agroforestry Sederhana di Widodomartani Ngemplak Sleman Yogyakarta Indonesia - Agus Prijono; Rawana; Yunianto Hargo Nugroho (Jurnal Wana Tropika, 2023)
Another Components simple agroforestry at Widodomartani ngemplak sleman yogyakarta indonesia is Cassava. Cassava for food can increase value economic with feed silkmoth samia ricini. The background that thus will sericulture  Samia ricini. The aims research were to determine time and product sericulture samia ricini. The method research  with sericulture samia ricini. The leaves cassava  for feed samia ricini. The  data collection on the time  for feed, percentage life larvae until coccon,  time results coccon, brieght coccon producted. The material researchers, larva Samia ricini 11 th day from 1 gr egg Samia ricini, the leaves cassava edibled and cassava karet non edible, with before feed leaves ricinus comunis. Samia ricini culture used silkmoth rearing rack. Results of the research showed that ecdysis procces 15 th day, after ecdysis increases actifity feeding very high until 21th day. Start coccon 22th day until 26th day the end larva last feeding leaves. The life percentage 95,87 %, feed cassava edible 94,89 %, an ond feed cassava non edible 96,53 %. The coccon producted start 22th day until 26th day , with weight rate coccon cassava edible 2.10264 gr, cassava non edible 2.109893 gr.